Infections after upper extremity allotransplantation: a worldwide population cohort study, 1998‐2017. (29th January 2019) - Conrad, Anne; Petruzzo, Palmina; Kanitakis, Jean; Gazarian, Aram; Badet, Lionel; Thaunat, Olivier; Vanhems, Philippe; Buron, Fanny; Morelon, Emmanuel; Sicard, Antoine
Summary: Risk‐to‐benefit analysis of upper extremity allotransplantation (UEA) warrants a careful assessment of immunosuppression‐related complications. This first systematic report of infectious complications after UEA aimed to compare incidence and pattern of infections to that observed after kidney transplantation (KT). We conducted a matched cohort study among UEA and KT recipients from the International Registry on Hand and Composite Tissue Transplantation and the French transplant database DIVAT. All UEA recipients between 1998 and 2016 were matched with KT recipients (1:5) regarding age, sex, cytomegalovirus (CMV) serostatus and induction treatment. Infections were analyzed at three posttransplant periods (early: 0–6 months, intermediate: 7–12 months, late: >12 months). Sixty‐one UEA recipients and 305 KT recipients were included. Incidence of infection was higher after UEA than after KT during the early period (3.27 vs. 1.95 per 1000 transplant‐days, P = 0.01), but not statistically different during the intermediate (0.61 vs. 0.45/1000, P = 0.5) nor the late period (0.15 vs. 0.21/1000, P = 0.11). The distribution of infectious syndromes was significantly different, with mucocutaneous infections predominating after UEA, urinary tract infections and pneumonia predominating after KT. Incidence of infection is high during the first 6 months after UEA. After 1 year, the burden of infections is low, with favorable patterns.